Descending necrotizing mediastinitis of oropharyngeal infections - Mohsen Sokouti; Saeed Nezafati (Journal of Dental Research, Dental Clinics, Dental Prospects, 2009)
Background and aims. Descending necrotizing mediastinitis (DNM) is a rare and life-threatening infection. Management of this condition is very difficult and before 1990s, DNM had a mortality rate of 40% despite the use of antibiotics. One of the etiologies of this condition is rapid downward spread of oropharyngeal infection along the cervical fascia planes into the mediastinum.
Materials and methods. Patients with DNM from odontogenic, peritonsillar and retropharyngeal origins, who underwent surgical treatment from 1990 to 2007, were reviewed. Data extracted from medical records of the patients included age, gender, origin of the infection, surgical approaches, and the cause of mortality. Descriptive data were expressed as a Mean ± SE.
Results. Thirteen patients aged 15 to 56 (mean, 34.5 years old; 8 males and 5 females) were studied. The origins of infection included odontogenic abscess in 10 cases and peritonsillar and retropharyngeal abscess in 3 patients. The mean duration from onset of symptoms to the surgery was 12.18 ± 0.98 days (range 3 to 24 days) and the mean duration from initial surgery to discharges was 28.51 ± 3.25 days (range 5 to 92 days). Post-operative mortality was seen in three patients.
Conclusion. Descending necrotizing mediastinitis can arise from odontogenic abscesses and must be detected as early as possible, as it is a life-threatening infection.